2018
DOI: 10.1134/s1070363218040308
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Styrene with Chlorine Dioxide

Abstract: Abstract-Reaction of styrene with chlorine dioxide under various conditions selectively produces 1-phenyl-2-chloroethanone, with 1-phenyl-2-chloroethanol, 2-hydroxy-1-phenylethanone, (1,2-dichloroethyl)benzene, (2-chloro-1-phenyl)ethene, and (1,2,2-trichloroethyl)benzene isolated as reaction byproducts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 19 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The resulting products were isolated in good to excellent yields (80–87%). This route stood out due to its mild reaction conditions and good efficiency, although it should be noted that TsNBr 2 is not readily accessed [ 147 , 148 ]. In 2017, Loginova et al reported a ClO 2 -mediated oxidative chlorination of styrene [ 149 ].…”
Section: Oxyhalogenation Of Hydrocarbonsmentioning
confidence: 99%
“…The resulting products were isolated in good to excellent yields (80–87%). This route stood out due to its mild reaction conditions and good efficiency, although it should be noted that TsNBr 2 is not readily accessed [ 147 , 148 ]. In 2017, Loginova et al reported a ClO 2 -mediated oxidative chlorination of styrene [ 149 ].…”
Section: Oxyhalogenation Of Hydrocarbonsmentioning
confidence: 99%